2016
DOI: 10.1007/s00410-016-1257-5
|View full text |Cite
|
Sign up to set email alerts
|

A chilled margin of komatiite and Mg-rich basaltic andesite in the western Bushveld Complex, South Africa

Abstract: and the elevated Sr and S isotopic signatures of the rocks. However, in order to account for the high Pt and Pd contents of the magma, the mantle must have been twice as rich in PGE as the current estimate for PUM, possibly due to a component of incompletely equilibrated late veneer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 61 publications
1
21
0
Order By: Relevance
“…Based on similarities between the composition of the Uitkomst chilled margins and the high-magnesian andesitic Bushveld B1 magmas, Gauert et al (1995) Yudovskaya et al 2015;Maier et al 2016). The Uitkomst intrusion data are modelled here in terms of prospective mixtures of mantle-derived magma (either a LREE-depleted asthenospheric mantle or an enriched, source-contaminated mantle) and Meso-to Neoarchaean crust consistent with the host rocks to the intrusion (Fig.…”
Section: Constraints On Parent Magma Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on similarities between the composition of the Uitkomst chilled margins and the high-magnesian andesitic Bushveld B1 magmas, Gauert et al (1995) Yudovskaya et al 2015;Maier et al 2016). The Uitkomst intrusion data are modelled here in terms of prospective mixtures of mantle-derived magma (either a LREE-depleted asthenospheric mantle or an enriched, source-contaminated mantle) and Meso-to Neoarchaean crust consistent with the host rocks to the intrusion (Fig.…”
Section: Constraints On Parent Magma Compositionmentioning
confidence: 99%
“…Because the trace element patterns of the Uitkomst and Bushveld cumulates show good overlap with upper crust (Maier et al 2000;Barnes et al 2010;Maier et al 2016) the latter model is favoured here. Additional contamination of the magnesian andesitic parent melt by a small amount (<5-15%) of roof-or wall-sedimentary rocks occurred during final emplacement.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More recent studies by Wilson (2012) and Maier et al (2016a) concluded that the most likely parental magma to the LZ would have been a komatiitic one with 18-19 wt% MgO derived from the asthenosphere, which assimilated some continental crust.…”
Section: Geological Settingmentioning
confidence: 99%
“…Per peridotite, Px pyroxenite, No norite, ol olivine, opx orthopyroxene, oth other minerals at the base of the LZ, consisting of a ca. 90-cm-thick chill sequence comprising Mg-rich basaltic andesite and komatiite (Maier et al 2016a). This is overlain by a ca.…”
Section: Geology Of the Lower Zonementioning
confidence: 99%